2019
DOI: 10.3762/bjnano.10.217
|View full text |Cite
|
Sign up to set email alerts
|

Design and facile synthesis of defect-rich C-MoS2/rGO nanosheets for enhanced lithium–sulfur battery performance

Abstract: We report a simple one-step hydrothermal strategy for the fabrication of a C-MoS2/rGO composite with both large surface area and high porosity for the use as advanced electrode material in lithium–sulfur batteries. Double modified defect-rich MoS2 nanosheets are successfully prepared by introducing reduced graphene oxide (rGO) and amorphous carbon. The conductibility of the cathodes can be improved through the combination of amorphous carbon and rGO, which could also limit the dissolution of polysulfides. Afte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Figure b shows the Raman spectra of the 2H and 1T MoS 2 phases, respectively. The Raman shifts of the 2H MoS 2 located at 380.9 and 406.7 cm –1 are related to the out-of-plane Mo–S mode (A 1g ) and in-plane Mo–S phonon mode (E 2g 1 ), respectively. , Obviously, the strong Raman bands at 199.7, 225.3, and 353.7 cm –1 are also identified, suggesting the formation of the 1T MoS 2 phase in the CF@2H/1T MoS 2 composite. , In addition, the Raman spectra of CF@2H/1T MoS 2 and CF exhibit two broad bands at 1349 (D-band) and 1579 cm –1 (G-band), which can be attributed to defect-induced vibrations and in-plane vibrations of sp 2 -hybridized carbon atoms in CF 3D network structure. , …”
Section: Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure b shows the Raman spectra of the 2H and 1T MoS 2 phases, respectively. The Raman shifts of the 2H MoS 2 located at 380.9 and 406.7 cm –1 are related to the out-of-plane Mo–S mode (A 1g ) and in-plane Mo–S phonon mode (E 2g 1 ), respectively. , Obviously, the strong Raman bands at 199.7, 225.3, and 353.7 cm –1 are also identified, suggesting the formation of the 1T MoS 2 phase in the CF@2H/1T MoS 2 composite. , In addition, the Raman spectra of CF@2H/1T MoS 2 and CF exhibit two broad bands at 1349 (D-band) and 1579 cm –1 (G-band), which can be attributed to defect-induced vibrations and in-plane vibrations of sp 2 -hybridized carbon atoms in CF 3D network structure. , …”
Section: Results and Discussionmentioning
confidence: 94%
“…36,39 In addition, the Raman spectra of CF@2H/1T MoS 2 and CF exhibit two broad bands at 1349 (D-band) and 1579 cm −1 (G-band), which can be attributed to defect-induced vibrations and inplane vibrations of sp 2 -hybridized carbon atoms in CF 3D network structure. 40,41 The high-resolution spectra of C 1s are illustrated in Figure S3a,c. The peaks at 284.8, 286.1, 288.0, and 289.7 eV correspond to the CC, CN, CN, and OCO species, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To investigate the electrochemical performance of the cathode prepared from CC@NS materials, CC@NS‐ n ( n = 0.1) is further investigated by CV on assembled C2032 button cells with a sweep rate of 0.1 mV s −1 . The results of the first seven cycles (Figure 7e) show that the electrode cathode peak appears at 2.34 and 2.03 V, corresponding to the reaction of elemental sulfur to soluble polysulfide intermediate (Li 2 S x , X ≥ 4) and the formation of the short‐chain insoluble solid product Li 2 S 2 /Li 2 S. As the scanning direction reverses, one anodic peak can be observed at 2.44 V, which is related to the oxidation of Li 2 S 2 /Li 2 S to polysulfide and further oxidation to element S. [ 25 ] The sharp and highly coincident CV curve indicates the reversible cycling of the positive electrode material and good redox kinetics. The redox peak shift can be attributed to the step‐wise reaction of the element sulfur after the electrolyte is infiltrated into the porous skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…MoS 2 , as a representative two-dimensional (2D) layered material, has an effective catalytic effect and strong chemical binding toward soluble LiPSs. , Notably, the binding energy of LiPSs to the Mo- and S-edge sites is much greater than that to the MoS 2 terrace site, which indicated that generating MoS 2 with higher edge site availability is helpful for trapping LiPSs. ,, Generally, the synthesized MoS 2 consisted of micrometer-sized aggregates that reduced the amount of active edge sites, resulting in an inferior catalytic activity in LSBs . Therefore, it is highly desirable to construct defect-rich MoS 2 nanosheets to increase the exposure of active edge sites . In addition, the limited conductivity nature of MoS 2 nanosheets also greatly restricts the immobilization and catalytic conversion of LiPSs .…”
Section: Introductionmentioning
confidence: 99%
“…27 Therefore, it is highly desirable to construct defect-rich MoS 2 nanosheets to increase the exposure of active edge sites. 28 In addition, the limited conductivity nature of MoS 2 nanosheets also greatly restricts the immobilization and catalytic conversion of LiPSs. 29 By contrast, heteroatom-doped carbon materials, especially N-doped carbon materials, possess not only strong chemisorption for LiPSs by an Li−N bond but also high electronic conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%